2000
DOI: 10.1161/01.str.31.8.1965
|View full text |Cite
|
Sign up to set email alerts
|

Serial MRI After Transient Focal Cerebral Ischemia in Rats

Abstract: Background and Purpose-With the advent of thrombolytic therapy for acute stroke, reperfusion-associated mechanisms of tissue injury have assumed greater importance. In this experimental study, we used several MRI techniques to monitor the dynamics of secondary ischemic damage, blood-brain barrier (BBB) disturbances, and the development of vasogenic edema during the reperfusion phase after focal cerebral ischemia in rats. Methods-Nineteen Sprague-Dawley rats were subjected to transient middle cerebral artery oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
148
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(169 citation statements)
references
References 60 publications
20
148
1
Order By: Relevance
“…31,32 Many previous studies have reported significantly decreased ADC and R 2 in cases of overt BBB disruption, suggesting that these parameters may be correlative indices for describing strokeinduced BBB damage. [13][14][15][16][17] On the contrary, in the current study, we observed similar infarct ADC and R 2 values that were independent of the WEI. The discrepancy principally results from different scales of BBB injury between studies.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…31,32 Many previous studies have reported significantly decreased ADC and R 2 in cases of overt BBB disruption, suggesting that these parameters may be correlative indices for describing strokeinduced BBB damage. [13][14][15][16][17] On the contrary, in the current study, we observed similar infarct ADC and R 2 values that were independent of the WEI. The discrepancy principally results from different scales of BBB injury between studies.…”
Section: Discussioncontrasting
confidence: 72%
“…According to previous study results, alterations in CBV, ADC, and R 2 were positively predictive of BBB disruption, as all of these parameters significantly decreased in ischemic stroke characterized by extravasation of contrast materials. [13][14][15][16][17] However, under such heavy ischemic stresses that lead to overt vascular disruption, changes in these MRI parameters may be derived not only from the weakened BBB itself, but also from other ischemia-affected tissue/vascular conditions including cytotoxicity, inflammation, and edema formation. 3,18,19 Therefore, overly simplified dichotomous division of stroke cases according to the presence of apparent trans-BBB leakage does not definitively identify the causative factors in the BBB disruption.…”
Section: Introductionmentioning
confidence: 99%
“…In shorter follow-up MR time series after MCAO (7 days), incomplete recovery of T 1 and T 2 values has been observed in some studies after transient (Neumann-Haefelin et al, 2000) and even permanent (Helpern et al, 1993;Knight et al, 1991) MCAO in rats. Knight et al (1994) described a heterogeneous response of MR relaxation times to MCAO, and noted large increases in T 2 times in the dorsolateral striatum with only moderate histological damage.…”
Section: Lesion Developmentmentioning
confidence: 98%
“…'Apparent' lesion volumes as well as relaxation times decrease slightly thereafter, and stabilize or increase again slightly (when cysts are formed) over the next 2 weeks (Ishii et al, 1998;Li et al, 2000;Lin et al, 2002a, b;Neumann-Haefelin et al, 2000;Palmer et al, 2001;van Dorsten et al, 2002;Virley et al, 2000). Even though T 1 -w and T 2 -w MRI have been shown to closely reflect the extent of irreversibly damaged tissue in the past, there is evidence that this correlation will not always hold in certain brain regions and at later time points (Knight et al, 1994;Neumann-Haefelin et al, 2000). Paramagnetic properties of inflammatory cells or blood degradation products, as well as regionspecific changes in water content and breakdown of macromolecular structures with influence on relaxation times, have been discussed as possible reasons for this phenomenon (Dijkhuizen et al, 1998;Lin et al, 2002a).…”
Section: Lesion Developmentmentioning
confidence: 99%
“…The same anesthesia procedure was repeated at the 24 h follow-up MRI. T 2 -hyperintensity was used to quantify infarction, which has been shown to be a reliable approach (Neumann-Haefelin et al, 2000;Palmer et al, 2001;van Dorsten et al, 2002).…”
Section: Animal Modelmentioning
confidence: 99%